Low birth weight and health expenditures from birth to late adolescence - Michael Hummer; Thomas Lehner; Gerald J. Pruckner (Johannes Kepler University of Linz, Department of Economics, 2012)
Using administrative panel data of health insurants, we estimate the effects of low birth weight on health service utilization among children and young adults between birth and 21 years old. To account for time-invariant heterogeneity of mothers, we use sibling fixed- effects estimation. We find that low birth weight strongly increases subsequent health expenditures and that the effect is particularly pronounced in the first year of life. Starting in compulsory schooling, we observe a shift in expenditures to mental-health problems. Whereas the effects on physical health disappear over time, we provide evidence that mental-health problems prevail until early adulthood. We therefore suggest a screening program tailored to the conditions more likely to be contracted by low-birth-weight children in order to mitigate the negative health consequences.
Keywords: I10; I12; I18; 330; Low birth weight; health expenditures; sibling fixed-effects; Geburtenrate; Gesundheitskosten; Statistische Methode; Österreich